2004
DOI: 10.1029/2004ja010471
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of magnetospheric electron density and irregularities at altitudes <5000 km using whistler and Z mode echoes from radio sounding on the IMAGE satellite

Abstract: [1] When the Radio Plasma Imager (RPI) on the IMAGE satellite operates in the inner plasmasphere and at moderate to low altitudes over the polar regions, pulses emitted at the low end of its 3-kHz to 3-MHz sounding frequency range can propagate in the whistler mode and/or in the Z mode. During soundings with both 25.6-ms pulses and 3.2-ms pulses, whistler mode echoes have been observed in (1) ''discrete,'' lightning whistlerlike forms and (2) diffuse, widely time spread forms suggestive of mode coupling at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 68 publications
2
46
0
Order By: Relevance
“…Then, near ω pi , the variation of |α x | around unity will not be smooth if µ is not small -what is typical of the Earth magnetosphere at altitudes below 4000 km (Sonwalkar et al, 2004). Actually, the large axis of the magnetic field polarization ellipse performs a rotation of π/2 when the frequency crosses the local ion plasma frequency ω pi ; the ellipse becomes a circle exactly at ω pi .…”
Section: Appendix C On the Variation Of The Magnetic Field Polarizatimentioning
confidence: 99%
“…Then, near ω pi , the variation of |α x | around unity will not be smooth if µ is not small -what is typical of the Earth magnetosphere at altitudes below 4000 km (Sonwalkar et al, 2004). Actually, the large axis of the magnetic field polarization ellipse performs a rotation of π/2 when the frequency crosses the local ion plasma frequency ω pi ; the ellipse becomes a circle exactly at ω pi .…”
Section: Appendix C On the Variation Of The Magnetic Field Polarizatimentioning
confidence: 99%
“…1.17 are also observed on IMAGE. They are called diffuse W-mode echoes [Sonwalkar et al,62]. In regions poleward of the plasmasphere, diffuse Z-mode echoes of the kind illustrated in Fig.…”
Section: Whistler-and Z-mode Echoesmentioning
confidence: 99%
“…In an investigation of IMAGE/RPI data in the inner plasmasphere and at moderate to low altitudes over the polar regions, Sonwalkar et al [62] found diffuse Z-mode echoes often accompanied whistler (W)-mode echoes. An example from their study is shown in Fig.…”
Section: Whistler-and Z-mode Echoesmentioning
confidence: 99%
“…This condition is indispensable, particularly for the near-Earth plasma at altitudes where the transition occurs from the lightest ions' to the more heavy ions' prevalence, i.e. typically at altitudes of few thousands kilometers above the Earth (Sonwalkar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In an inhomogeneous magnetospheric plasma, the sources of whistler emissions can be located far from the region where the wave emissions effectively reveal their properties and are registered by remote receivers. Then the GO approach is conventionally used to solve the problem of the spectral characteristics' evolution of the emissions during their distant propagation from their sources; it was also used effectively in the recent active radio sounding projects similar to that one realized on board the IMAGE satellite (Burch, 2000;Reinish, 2000;Sonwalkar et al, 2004;Carpenter, 2004). Moreover, the GO technique was also applied to fit the parameters of space density model distributions using the Direction Finding Data of groundbased transmitter signals registered on board the "Ikebono" satellite (Sawada et al, 1993).…”
Section: Introductionmentioning
confidence: 99%